The Impact of Ergonomics Driving Risk Factors on Musculoskeletal Health of Malaysian Express Bus Drivers - Yusof, Hashim; Zahari, Taha (Universiti Selangor (UNISEL), 2014)
The purpose of this paper is to assess the impact of ergonomics driving risk factors on musculoskeletal health of Malaysian express bus drivers. A survey research was carried out among express bus drivers operating in Kuantan, Pahang and several major cities in West Coast. This is to determine the prevalence of musculoskeletal pain and to identify ergonomic driving risk factors that are likely to increase the risk of neck, shoulder or lower back pains. Seventy-nine bus drivers were selected and interviewed in the survey. The study instrument was based on the Occupational Factors, Ergonomic Driving Risk Factors and Nordic Musculoskeletal Questionnaires. The SPSS version 17 was used to analyze the descriptive characteristics of the demographic information of the respondents while the relationships between the latent constructs were analyzed by SmartPLS software. The finding of the research showed that there is a significant and positive relationship between ergonomic driving risk factors and musculoskeletal pains. However, the occupational factor is not significantly correlated to ergonomic risk factors. In conclusion, this study is of particular relevance and important for specific government agency as accidents that involved the public transports in Malaysia are increasing.